Erector Spinae Plane Block for Lumbar Spinal Surgery: A Systematic Review - Yong Qiu; Teng-Jiao Zhang; Zhen Hua (2020)
Background: Erector spinae plane block (ESPB) as a new trunk fascia block technique was proposed in 2016. ESPB has aroused the interest of many nerve block experts. However, there are few clinical studies on ESPB for lumbar surgery, and its effectiveness and safety are controversial. The goal of this review is to summarize the use of ESPB for lumbar spine surgery in order to better understand this technique. Methods: PubMed, EMBASE, Cochrane library and ClinicalTrial.gov databases were searched up to July 30, 2019. According to the inclusion and exclusion criteria established in advance, “lumbar spine surgery” and “ESPB” related MesH terms and free-text words were used. Data on pain scores, analgesic consumptions and adverse effects were reported. All processes follow PRISMA statement guidelines. Results: A total of 171 participants from 11 publications were identified, including two randomized controlled trials (RCTs), one retrospective cohort study, four case reports and four cases series. Block operation planes from T8 to L4. The main anesthetics used in the block are bupivacaine, ropivacaine and lidocaine. There was evidence for reducing postoperative pain scores and analgesic consumptions. Conclusion: The effectiveness and safety of ESPB for lumbar spine surgery are still controversial. The current evidence is insufficient to support the widespread use of ESPB for lumbar spine surgery. High-quality RCTs are urgently needed. Keywords: ESPB, lumbar spine surgery, postoperative analgesia